A new version of energy for involute of slant helix with bending energy in the Lie groups (Acta Scientiarum. Technology, 2019)
In this paper, we study energy of involute curves for slant helix in the Lie group. With this new representation, we illistrate some figures of energy by elastica. Finally, we have an original and satisfactorily connection between energy of the curve on Lie groups.